Acoustic analysis of clients’ expression of self-compassion, self-criticism, and self-protection within emotion focused therapy video sessions - Bailey, Ghazaleh; Halamová, Júlia; Vráblová, Viktória (Frontiers in Psychology, 2024)
Introduction When it comes to the non-verbal communication of emotions, it is apparent that the human voice is one of the main ways of expressing emotion and is increasingly important in psychotherapeutic dialog. There is ample research focusing on the vocal expression of emotions. However, to date the analysis of the vocal quality of clients’ in-sessional emotional experience remains largely unexplored. Moreover, there is generally a gap within the psychotherapy literature in the understanding of the vocal character of self-compassion, self-criticism, and protective anger. Methods In this study we investigated how clients vocally convey self-compassion, self-protection and self-criticism in Emotion Focused therapy sessions. For this purpose we investigated 12 commercially available Emotion Focused Therapy videos that employed a two chair or empty chair dialog. Praat software was used for the acoustic analysis of the most common features – pitch (known as fundamental frequency or F0) and intensity (voice amplitude, i.e., loudness). Results Results showed that intensity was significantly higher for self-criticism and self-protection than for self-compassion. Regarding pitch the findings showed no significant differences between the three states. Discussion More research analyzing acoustic features in a larger number of cases is required to obtain a deeper understanding of clients’ vocal expression of self-compassion, self-protection and self-criticism in Emotion Focused Therapy.